Evaluation of the antioxidant potential and antibacterial activity of the pulp extract of Psidium brownianum Mart. ex DC (Research, Society and Development, 2020)
Species of the genus Psidium have come out to be efficient in terms of characteristics of nutritional interests, such as richness in vitamins and antioxidants. In addition, antibacterial activity has been evidenced by extracts from species of the genus Psidium. Thus, the present study aims to evaluate the antioxidant potential and antibacterial activity of Psidium brownianum Mart pulp extract. ex DC .. The total phenolic compounds were quantified by using the Folin - Ciocalteau reagent. The antioxidant potential of Psidium brownianum Mart. ex DC. was determined by the photocolorimetric method in vitro by sequestrating the stable free radical DPPH. To evaluate the antibacterial capacity of the extract, it was used the broth microdilution method. The total phenolic compounds found in the extract represent the value of 1211 mg GAE / 100 g of the sample. The extract of Psidium brownianum Mart. ex DC. Presented a high antioxidant potential, probably due to its high content of phenolic compounds. The species also evidenced inhibitory activity against all tested bacterial strains. According to this, it is possible to infer that the pulp of Psidium brownianum Mart. ex DC., comes out to be a rich source of total phenolic compounds and antioxidant potential, so ingesting it is important. As for antibacterial activity, further studies are needed involving possible associations of this extract with other substances, as a way to enhance its use.